An industry-level analysis of the post-Brexit and post-Covid 19 Ro-Ro ferry market and critical maritime freight transport links between the UK and the EU - Dimitrios Paraskevadakis; Adeyeri Ifeoluwa (Journal of Shipping and Trade (JST), 2022)
Evaluating supply chain system improvements and international economic integration patterns to changes in expenditure requires urgent attention from short to long-term supply chain disruption review. Following the United Kingdom's exit from the European Union, the UK and the global economies have been affected. Brexit has affected sectors that rely on cross-border commerce with EU countries, while services that require face-to-face interaction have been negatively impacted by Covid 19. For example, the Roll on Roll off (RoRo) ferry sector has suffered tremendously from the Covid 19 pandemic, which restricts people's travel, and Brexit, which results in the UK having a geographical barrier with the rest of the EU continent. The study examines the ferry RoRo market, maritime links, and its viability in the face of Brexit and the Covid issue between the United Kingdom and short-sea shipping connections with Ireland and continental Europe. Understanding the market is critical since roll-on roll-off (Ro-Ro) traffic plays a significant part in the movement of products between the UK and the EU. Adopting a method mapping provided a defined research paradigm for this study. Mixed-method design technique, a branch of multiple methods research, was employed, resulting in a better understanding of the research topic. The findings demonstrate that nations and the RoRo freight supply chain network have been significantly impacted. However, continuous measures are implemented to ensure continuous freight movement. The study obtained data from 14 respondents and was statistically analysed. The results demonstrate that an organisation's capacity to manage these disturbances significantly impacts its survivability. It also indicates that the government's awareness of the implications of Brexit and Covid 19 significantly determines the impact on organisations. This research concludes that the impact on organisations is minimal, notwithstanding the effects of Brexit and Covid. However, owing to uncertainties, continuous methods for continuous freight transit should be implemented, together with an adequate flow of information.
Keywords: 650; Short sea shipping; Covid-19; Brexit; Freight ferries; Ferry routes; Global trade; Intermodal transport; Logistics